Lace Narratives A Monograph, 2005 - 2015 - Heffer, Cecilia (UTS ePRESS, 2015)
Lace Narratives: A monograph, 2005 - 2015 documents Cecilia Heffer's innovative lace-making practice over a decade, including major exhibitions and commissions. This publication examines ways that Cecilia's research practice responds to changing ideas and technologies as a means to extend our perception of textiles. It presents an in-depth reflection on studio practice in a discursive spirit, responding to the question: What has the studio enquiry revealed that could not have been revealed through other modes of research? The publication is composed of a digital edition of the book, along with a seven-minute video documenting Cecilia creating the lace-work Drawn Threads. A print-on-demand version of the book in either hard cover or paperback is available for purchase. Additionally, a limited edition artist's book with lace samples bound into the pages will be publicly available through selected libraries and museums, including the UTS Library. Through these different components, the audience can watch Cecilia's lace-making innovations in the documentary video, read critical reflections on her research and creative process, and handle lace samples. This combination affords a holistic understanding of Cecilia's practice-led research and material output. This is an experimental publication model conceived by Zoë Sadokierski for the MediaObject book series and produced with support from the UTS Library.